Sikap terhadap Electronic Money dilihat dari Persepsi Manfaat dan Persepsi Kemudahan - Amirah Aprilria Kusnadi; Arlin Ferlina Mochamad Trenggana (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
The COVID-19 virus causes social restrictions that make people minimize the use of cash when shopping. E-money is one of the payment instruments whose use during the early 2020 period decreased. The study was conducted to determine and analyze attitudes toward use, perceived usefulness, and perceived ease of use. The research uses quantitative, descriptive, and causal methods. The population is the people of Bandung city who have E-money, while the data collection is done by cluster sampling with 385 questionnaire results obtained through an online survey using google form. Multiple linear analysis is used to process data with known results, perceptions of benefits and convenience play a role in user attitudes either partially or simultaneously. The results of the study are expected to be a recommendation for E-money providers to pay attention to the benefits and convenience of services to improve usage attitudes in adopting E-money services